Pyridoxamine improves diabetes-evoked delayed bone repair in mice. Issue 3 (2021) - Ugaji, Shuhei; Kimura, Kumi; Yamamoto, Yasuhiko; Munesue, Seiichi; Harashima, Ai; Aikawa, Takao
No abstract available